2008
DOI: 10.1136/ip.2008.018820
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the burden of road traffic injury: translating high-income country interventions to middle-income and low-income countries

Abstract: Objective: To increase seat belt restraint use in Guangzhou City, People's Republic of China. Design: Comparison group pre-test, post-test design. Setting: Guangzhou City. Interventions: Interventions to increase the prevalence of seat belt use in high-income countries (enhanced training and enforcement practices along with raising of public awareness) were adapted and implemented in Guangzhou. The prevalence of seat belt use was determined before and after the introduction of the 12-month intervention. Seat b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…Stevenson et al (2008) measured ICERs with the net costs and benefits of comprehensive seatbelt interventions compared with no interventions to promote seat belt use. Chisholm et al (2012) reported ICERs briefly in the table with no numerical value of ICERs provided.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Stevenson et al (2008) measured ICERs with the net costs and benefits of comprehensive seatbelt interventions compared with no interventions to promote seat belt use. Chisholm et al (2012) reported ICERs briefly in the table with no numerical value of ICERs provided.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…All studies except Ditsuwan et al (2013) did not state the discount rate, or conduct sensitivity analyses. Three out of five studies had a time horizon of one year (Bishai and Hyder 2006;Ditsuwan et al 2013;Stevenson et al 2008), one study had time horizon of 10 years (Chisholm et al 2012), and one was unreported (Bishai et al 2008). All future costs and consequences (DALYs and/or life year saved) were discounted to present values at an annual rate of 3% by the studies that reported discounting in their studies (Bishai and Hyder 2006;Bishai et al 2008;Chisholm et al 2012;Ditsuwan et al 2013).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations